Pengaruh Citra Merek Dan Kualitas Layanan Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Mediator Pada Klinik Kecantikan London Beauty Center - Rosyidah Aulia (PRAGMATIS, 2022)
This study aims to 1) Determine if brand image has a substantial impact on client loyalty at the London Beauty Center. 2) Determine if service quality has a substantial impact on client loyalty at the London Beauty Center. Determine if brand image has a substantial impact on customer satisfaction at the London Beauty Center. 4) Determine the significance of the relationship between service quality and client happiness at the London Beauty Center. 5) Determine the relationship between client satisfaction and customer retention at the London Beauty Center. 6) Determining the role of customer satisfaction as an intermediary between brand image, service quality, and customer loyalty at the London Beauty Center. In this research, the independent variables are brand perception and service quality. Customer loyalty is the dependent variable in this research. In this research, the mediating variable or interrupting variable is customer happiness. Sampling was carried out using the Non-Probability Sampling method, with the criteria of consumers in Surabaya who had purchased products. The number of sampels 110 respondents. The analysis technique to test te hypothesis is using instrument test, hypothesis test, determinant coefficient test, sobel test, path analysis. The results indicated that service quality has a positive and statistically significant impact on customer loyalty, brand image has a positive and statistically significant effect on customer loyalty, service quality has a positive and statistically significant effect on customer satisfaction, brand image has a positive and statistically significant effect on customer satisfaction,and customer satisfaction has a positive and statistically significant effect. On customer loyalty, brand image and service quality are explained through customer satisfaction as a mediator.